Interaksi Antara Indikator Moneter Dan Indikator Makroekonomi di Indonesia Tahun 2005 – 2010 - Cahyadin, Malik; Awirya, Agni Alam (Jurnal Ekonomi Kuantitatif Terapan, 2012)
The objective of this research is to analyze the interaction (causality) and the interconectivity (correlation) between monetary and macroeconomy indicators, using two categorized data: monetary block and macroeconomy block from 2005 to 2010. The method which used to analyze are Granger causality and Correlation method. The results of this research are: (1) monetary indicators that have causality interaction to macroeconomy indicators from 2005 to 2010 are: BI rate with P, BI rate with X, ER with GPDB, ER with M, Money Supply with P, Money Supply with UE, inflation with P, inflation with X; (2) monetary indicators that have a strong correlation to macroeconomy indicators from 2005 to 2010 are: BI rate with M, BI rate with UE, BI Rate with X, inflation with UE, Money Supply with M, Money Supply with P, Money Supply with UE and Money Supply with X.
Keywords: monetary indicators; macroeconomy indicators; granger causality; correlation